Birth control pills and risk of hypothyroidism: a cross-sectional study of the National Health and Nutrition Examination Survey, 2007–2012. Issue 6 (23rd June 2021) - Qiu, Yuxuan; Hu, Yuanyuan; Xing, Zhichao; Fu, Qingyu; Zhu, Jingqiang; Su, Anping
Abstract : Objective: The association between use of birth control pills and thyroid function in women has not ever been well studied, but potential risk has been implicated by small sample-sized studies. We aimed to determine this association using a large epidemiological survey. Design: Cross-sectional study. Setting: National Health and Nutrition Examination Survey conducted in the USA from 2007 to 2012. Participants: Female respondents aged 18+ who had data on history of taking birth control pills and thyroid function were included. History of taking birth control pills was based on responses on the reproductive health questionnaire. Participants not on antithyroid medication with thyroid-stimulating hormone (TSH) >5.6 mIU/L and those on thyroid hormone replacement regardless of TSH were categorised as hypothyroid. Participants not on thyroid hormone replacement or antithyroid medication who had TSH between 0.34 mIU/L and 5.6 mIU/L were classified as euthyroid. Primary and secondary outcome measures: Association between use of birth control pills and hypothyroidism based on multivariate logistic regression analysis. Results: A total of 5116 female adults with history of taking birth control pills (n=3034) and without (n=2082) were included. A higher prevalence of hypothyroidism was found in those who have ever taken birth control pills (17.7% vs 14.1%; p=0.003). Multivariate logistic regression adjusted for confounding covariables, including age, race, education, body mass index, smoking status, alcohol use, history of thyroid disease, current thyroid disease, first menstrual age, pregnancy history, menopause status and history of hormone replacement use, demonstrated a significant association between history of taking birth control pills for more than 10 years and hypothyroidism (OR, 3.837; 95% CI 1.402 to 10.500; p=0.009). Conclusions: Longer history of using birth control pills was strongly associated with hypothyroidism, especially for more than 10 years.